An investigation of the petrogenesis of the Buddusò I-type granites and its mafic enclaves in Sardinia, Italy. - Soorajlal, Roxanne (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.